Benefits and risks of therapeutic alternatives for macrolide resistant pneumonia in children - Hyeon-Jong Yang (Korean Pediatric Society, 2019)
Although Mycoplasma pneumoniae pneumonia (MPP) has been generally susceptible to macrolides, the emergence of macrolide-resistant MPP (MRMP) has made its treatment challenging. MRMP rapidly spread after the 2000s, especially in East Asia. MRMP is more common in children and adolescents than in adults, which is likely related to the frequent use of macrolides for treating M. pneumoniae infections in children. MRMP is unlikely to be related to clinical, laboratory, or radiological severity, although it likely prolongs the persistence of symptoms and the length of hospital stay. Thereby, it causes an increased burden of the disease and poor quality of life for the patient as well as a societal socioeconomic burden. To date, the only alternative treatments for MRMP are secondary antimicrobials such as tetracyclines (TCs) or fluoroquinolones (FQs) or systemic corticosteroids; however, the former are contraindicated in children because of concerns about potential adverse events (i.e., tooth discoloration or tendinopathy). A few guidelines recommended TCs or FQs as the second-line drug of choice for treating MRMP. However, there have been no evidence-based guidelines. Furthermore, safety issues have not yet been resolved. Therefore, this article aimed to review the benefits and risks of therapeutic alternatives for treating MRMP in children and review the recommendations of international or regional guidelines and specific considerations for their practical application.